Narrative Review: Perancangan Sistem Pengisian Cepat untuk Kendaraan Listrik dengan Algoritma Kontrol Baterai - Namira Nurul Dania (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
In the future, electric vehicles will become the primary choice for transportation due to their environmentally friendly nature and zero carbon emissions. Electric vehicles use batteries as their main source of energy, which can be recharged by continuously flowing electric current. However, uncontrolled charging can cause overcharge to the battery. Therefore, this study aims to find an efficient strategy to control the voltage using fast charging algorithms for electric vehicles. The method used includes the design of a fast charging circuit, battery assembly, and fast charging testing. The results show that the fast charging circuit uses a buck converter circuit combined with a charger circuit to produce a specification of 48 Volts 6 Amperes. The capacitor and resistor components on the output affect the charging speed, and charging is considered fast charging when it reaches 40% battery capacity within 2 hours of charging.